Green Training and its Impact on the Sustainability of the Health Organization - Hayder Jasim Al-Juboory; Faris Hassan Eydan Eydan (مجلة الغري للعلوم الاقتصادية والادارية)
The main objective of this research is to build a sustainable health organization and to develop sustainability business through green training. To achieve this objective, the researchers surveyed the opinions of a number of employees who work at Najaf Health Directorate headquarter. The research community is (250) employees. The sample of the study is (155) analyzable valid responses. The researcher analyzed the data collected using tests and statistical methods powered by the (SPSS v.24) program. The study adopted one main hypothesis and three subhypotheses, which are the influence relationship among the variables of research. The hypotheses are to review the sustainability dimensions of the health organization, and the extent to which green training affect these dimensions. Finally, the research came up with a set of conclusions, the most important being that sustainability in the health organization is inevitable and not voluntary actions to engage the community's concerns and environmental concerns, as the lack of sustainability of the health organization means transforming it from an organization that tries to relieve the burden and pain of members of society to a bomb timethreatening ecological health. The recommendations touch the needs of the Directorate. The most important recommendation is to increase the number of the green training programs in a way that promotes the sustainability of the health organization. In addition, the research recommends adopting this concept (the green training) in the annual training plans.